The Development of Two-tier Multiple Choice Assessment Instrument to Measure Higher Order Thinking Skills (HOTS) of The Students on Excretion System Material - Yunita, Yunita; Dewi, Novi Ratna (Unnes Science Education Journal, 2020)
Science learning based on 2013 curriculum requires the students to be able at analyzing, evaluating, and creating to achieve higher order thinking skills (HOTS). The results of observation at SMP N 2 Sukolilo showed that there was no task or question which was specifically used to measure HOTS of the students. The aim of this study is to analyze the characteristics of two-tier multiple choice assessment instrument and HOTS ability of the students. This research was conducted by using Research and Development (R&D) method. Samples were taken by random sampling technique from the population of class IX students of SMP N 2 Sukolilo in the academic year 2019/2020, then class IX C was selected for small-scale trial, class IX B was selected for large-scale trial, and class IX A was selected for trial use. Data was taken by some methods such as test, questionnaire, and documentation. The characteristics of two-tier multiple choice assessment instrument was analyzed by expert judgment and empirical testing. Whereas, HOTS level of the students was analyzed using the HOTS Category Scale. The results of the analysis of the characteristics of two-tier multiple choice assessment instrument indicated that the developed instrument had fulfilled the requirement as a good instrument, namely (1) valid, with the result of expert validation as many as 79% (feasible) and the results of the item analysis was 0.49 (sufficient ); (2) reliable, with the reliability result was 0.40 (reliable); (3) relevant, representative, practical, and specific as indicated by the results of the teacher's questionnaire responses with the percentage 75% (good); (4) discriminatory power, with the average of analysis result was 0.36 (good); and (5) proportional / difficulty level, with the analysis result of most questions in the moderate category. Furthermore, the analysis results of HOTS level of the students showed that the students on the large-scale trial were mostly in the moderate category (67%) and some of them in a small portion were in the low category (33%). While, HOTS level of the students on the trial use showed that most of the students were in the moderate category (50%), some of them were in the low category (30%), and a small portion of them were in the high category (20%). The conclusion of this study is the developed two-tier multiple choice assessment instrument has been feasible, because it has met the requirements as a good instrument and can be used to measure HOTS of the students.